2000
DOI: 10.1161/01.cir.102.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Independent Prognostic Value of Cardiac Troponin T in Patients With Confirmed Pulmonary Embolism

Abstract: cTnT may improve risk stratification in patients with PE and may aid in the identification of patients in whom a more aggressive therapy may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
259
4
35

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(313 citation statements)
references
References 32 publications
15
259
4
35
Order By: Relevance
“…We have previously shown that acute myocardial infarction and ischemia can occur in sickle cell disease, independent of the acute chest syndrome [9][10][11][12]. Acute and chronic pulmonary hypertension have been shown to be associated with elevated troponin levels, indicating a poorer prognosis; however, the levels reported were small, possibly indicating leakage from a compromised right ventricle, in contrast to the levels in our cases which are compatible with significant tissue injury [13][14][15].…”
Section: Discussioncontrasting
confidence: 54%
“…We have previously shown that acute myocardial infarction and ischemia can occur in sickle cell disease, independent of the acute chest syndrome [9][10][11][12]. Acute and chronic pulmonary hypertension have been shown to be associated with elevated troponin levels, indicating a poorer prognosis; however, the levels reported were small, possibly indicating leakage from a compromised right ventricle, in contrast to the levels in our cases which are compatible with significant tissue injury [13][14][15].…”
Section: Discussioncontrasting
confidence: 54%
“…Recently, several studies observed elevated cardiac troponins especially in patients with RV overload, suggesting myocardial injury during the acute phase of APE. [12][13][14] Moreover, autopsy and scintigraphic case series reported RV MIs in patients with major APE. 15,16 Therefore, larger RV dimension and higher Tei index found at follow-up in the APE group may result from damage-induced RV remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Whichever the mechanism, elevated cardiac troponin is increasingly reported as a marker of poor prognosis also outside acute coronary syndromes. 4,19,23 It would be premature to formally recommend a place for cTnT assessment in clinical management of patients with PAH and CTEPH. However, detectable cTnT seems to convey an important message, indicating acceleration of the vicious circle of RV failure precipitating systemic hemodynamic collapse and death.…”
Section: Torbicki Et Al Ctnt As a Marker Of Risk In Chronic Precapillmentioning
confidence: 99%
“…In acute precapillary PH, such as attributable to an episode of pulmonary embolism, injury of myocytes evidenced by transient elevation of cardiac troponins was consistently reported and was related to increased in-hospital mortality. [3][4][5] The objective of our study was to check whether circulating cardiac troponins can be detected and might have clinical significance also in patients with RV overload attributable to chronic precapillary PH.…”
mentioning
confidence: 99%